A novel preparation of GO/NiFe2O4/TiO2 nanorod arrays with enhanced photocatalytic activity for removing unsymmetrical dimethylhydrazine from water. (January 2021) - Lu, Ya-bo; Wang, Huan-Chun; She, Xiang-yang; Huang, Dan; Yang, Yu-xue; Gao, Xin; Zhu, Zuo-ming; Liu, Xiang-xuan; Xie, Zheng
Abstract: We report a novel composite graphene oxide (GO)/NiFe2 O4 /TiO2 nanorod arrays (NRAs) prepared by calcinating and dipping, TiO2 NRAs were prepared via hydrothermal method. XRD, SEM, XPS, and PL, show that GO/NiFe2 O4 /TiO2 NRAs have been successfully synthesized having enhanced photocatalytic performance. Furthermore, the optimal degradation conditions of unsymmetrical dimethylhydrazine (UDMH) using the catalyst were obtained by orthogonal and single-factor experiment. Moreover, the possible photocatalytic mechanism is briefly discussed; under visible light, electrons and holes excited from NiFe2 O4 can be effectively separated due to the band energy matching between NiFe2 O4 and TiO2 . In addition, photogenerated electrons can quickly migrate to GO owing to the conduction band, as the position of NiFe2 O4 is more negative than the Fermi level of GO. The electrons and holes were well separated so that they can efficiently participate in the degradation of UDMH, resulting in enhancement of photocatalytic activity. Highlights: AA novel composite catalyst GO/NiFe2 O4 /TiO2 NRAs was prepared for the first time. It exhibits enhanced photocatalytic activity in degradation of UDMH, due to the efficient separation of carriers. The optimal degradation conditions of UDMH under this catalyst are also achieved.